(untitled) (Sciences & Technologie. C, Biotechnologies, 2007)
The experiment conducted in the Laboratory of Genetic, Biochémistry and plant Biotechnology (LGBBV), Faculty of Sciences, Mentouri University (Constantine) aimed to study the response of three olive cultivars (Olea europaeaL.) response to two basic tissue culture media complemented with different concentrations of growth regulators. Cuttings of Chemlal, Siguoise and Grosse de Hamma cultivars were collected from the Erkani Pilot Farm located at Hamma Bouziane. Under complete aseptic conditions explants 1cm long holding lateral buds were subcultured inMS and B5 media complemented with growth regulators. B5 medium emerged as the best for tissue culture of the studied cultivars. Based on leaf proliferation, stem extension and accumulated fresh matter measurements, Chemlal showed a good response to in vitro culture. Root proliferation was induced after callus formation for Chemlal in the 1/2 diluted MS medium complemented with 0.5 mg.l-1 Kinetine + 0.5 mg.l-1ANA and in B5 medium complemented with 0.4 mg.l-1BAP + 1.33 mg.l-1AIB. And for Sigoise in the 1/2 diluted MS medium complemented with 0.5mg.l-1Kinetine + 1 mg.l-1ANA. Leafed and rooted explants from the two cultivars have passed successfully the acclimation phase and fully adapted to grow under glasshouse conditions.